INDIVIDUAL INDICATORS OF METACOGNITIVE MONITORING OBJECTIVITY - Августюк, М. М. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2015)
The article provides theoretical analysis of the main approaches related to the problem of studying the role of individual indicators in metacognitive monitoring objectivity in the sphere of training activities. In particular, attention is drawn to such individual indicators that affect the objectivity of metacognitive monitoring in the sphere of training activities as intellectual capability, motivation to learn, self-assessment, sex differences, age, mood and so on. On the basis of the analysis it was found that overconfidence as an indicator of inaccuracies of metacognitive monitoring is especially common among individuals showing low levels of success. A special place in psychological and educational researches also the problem of self-assessment and motivation to learn, which are closely related to indicators of academic success, takes